2022
DOI: 10.1038/s41467-022-29103-z
|View full text |Cite
|
Sign up to set email alerts
|

In situ infrared nanospectroscopy of the local processes at the Li/polymer electrolyte interface

Abstract: Solid-state batteries possess the potential to significantly impact energy storage industries by enabling diverse benefits, such as increased safety and energy density. However, challenges persist with physicochemical properties and processes at electrode/electrolyte interfaces. Thus, there is great need to characterize such interfaces in situ, and unveil scientific understanding that catalyzes engineering solutions. To address this, we conduct multiscale in situ microscopies (optical, atomic force, and infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Previous results have suggested that the SEI is heterogenous on the nanoscale; , therefore, we aimed to use the high-resolution capabilities of the nano-FTIR to evaluate this assessment. We probed the film over a 200 nm line scan in 10 steps, close to the limit of the technique’s resolution …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous results have suggested that the SEI is heterogenous on the nanoscale; , therefore, we aimed to use the high-resolution capabilities of the nano-FTIR to evaluate this assessment. We probed the film over a 200 nm line scan in 10 steps, close to the limit of the technique’s resolution …”
Section: Resultsmentioning
confidence: 99%
“…The topography of the surfaces is very smooth, and the resulting spectra do not vary significantly in terms of peak ratios as a function of position. For the non-washed electrode (Figure 5a), the spectra were taken at a different location from Spot 1 (in Figure 3a sensitivity to molecular orientation, 19 we speculate that these variations originate from different conformations of the LiEDC and EC molecules on the surface/subsurface region. Furthermore, the nano-FTIR spectrum from each location has similar IR absorption peak characteristics as the bulk ATR-FTIR measurement (Figure 4), which indicates that the chemical composition, structure, and distribution of the organic compounds in the SEI of the non-washed a-Si electrode are fairly homogenous.…”
Section: Evaluation Of the Effects Of Dmc Washing On The Sei Layermentioning
confidence: 98%
See 3 more Smart Citations